Isotherm, kinetic and adsorption study of malachite green dye on Carbon Nanotubes Immobilized Biomass (CNTIB) - Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Al-Khatib, Ma An Fahmi Rashid (2017)
This study tries to assess wastewater quality in textile industry, one of the critical issues to be well thought-out is the exposure to chemicals substances, as it might represent a health concern in textile industry and is subject to different health occupational limits. This paper attempts to describe the factors which might have an impact in the textile industry as high concentration of non-biodegradable compounds contributes to increased biochemical oxygen demand (BOD) and chemical oxygen demand (COD) of the wastewater bodies. Dyes found in wastewater from textile industries are carcinogenic, mutagenic or teratogenic. Biological processes involving certain bacteria, fungi, activated carbon and carbon nanotubes (CNTs) are promising methods for treating waste water but these methods are either inefficient or ineffective. These complexities necessitates search for new approaches that will offset all the shortcomings of the present solutions to the challenges faced with textile wastewater management. Furthermore, the study produced a new biosorbent by the immobilization of fungal biomass on carbon nanotubes. The new biosorbent is called “carbon nanotubes immobilized biomass (CNTIB)”. The biosorbent was produced by immobilization technique. A potential fungal strain, Aspergillus niger was selected on the basis of biomass production. Aspergillus niger was immobilized on carbon nanotubes. Isotherm studies showed that the experimental data better fitted with the Langmuir isotherm for CNTIB (R2= 0.919) when compared to Freundlich isotherm (R2= 0.892). Notwithstanding the aforementioned information, the kinetic study however indicated that the biosorption followed the pseudo-second order kinetic model which suggests that chemisorption is most likely the process through which biosorption took place.